Pelatihan Microsoft Word Untuk Menunjang Kemampuan Administrasi Pengurus IP3NN Di Pesantren Nafidatunnajah - A. Nurul Anwar; Saprudin; Dani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The advent of the revolution demands that people, both students and workers, be highly competitive and possess the necessary skills to navigate the sophistication of this digital era. Information and communication technology (ICT) has transformed the way student administration is conducted. With information technology, previously manual administrative processes can now be automated. For example, managing correspondence, archiving, and data management can be done using specially designed applications, namely Microsoft Office. Good administrative skills are a crucial factor in organizational management. In the digital era, mastery of technology, especially word processing applications like Microsoft Word, is a primary requirement to support administrative activities, such as creating reports, correspondence, and other documents. Optimal use of Microsoft Word can increase efficiency in compiling documents with neat and professional formats. However, many IP3NN administrators still lack a thorough grasp of Microsoft Word. This can hinder the effectiveness of their work in compiling and managing administrative documents. Therefore, this training aims to improve the administrative skills of IP3NN administrators in using Microsoft Word so they can work more efficiently, productively, and professionally. With this training, it is hoped that administrators will be able to utilize Microsoft Word's features to their full potential to support the smooth running of their organization's administration.